2015
DOI: 10.1152/japplphysiol.00045.2015
|View full text |Cite
|
Sign up to set email alerts
|

Activation of α1-adrenoceptors facilitates excitatory inputs to medullary airway vagal preganglionic neurons

Abstract: In mammals, the neural control of airway smooth muscle is dominated by a subset of airway vagal preganglionic neurons in the ventrolateral medulla. These neurons are physiologically modulated by adrenergic/noradrenergic projections, and weakened α₂-adrenergic inhibition of them is indicated to participate in the pathogenesis and exacerbation of asthma. This study tests whether these neurons are modulated by α₁-adrenoceptors, and if so, how. In anesthetized adult rats, microinjection of the α₁A-adrenoceptor ago… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 34 publications
(45 reference statements)
1
10
0
Order By: Relevance
“…However, we report that A61603, an α1A agonist, increased sEPSC but did not alter the frequency of sIPSC. Such an excitation effect through α1A receptors has been reported in other CNS regions (11,31).…”
Section: Synaptic Current Modulation Of Nasupporting
confidence: 70%
“…However, we report that A61603, an α1A agonist, increased sEPSC but did not alter the frequency of sIPSC. Such an excitation effect through α1A receptors has been reported in other CNS regions (11,31).…”
Section: Synaptic Current Modulation Of Nasupporting
confidence: 70%
“…One study found that thyrotropin-releasing hormone significantly suppressed the inspiratory outward currents of II-AVPNs while has no effect on their sIPSCs (Hou et al, 2012 ). Another found that an agonist of α 1 -adrenoceptors significantly enhanced the inspiratory outward currents of II-AVPNs but had no effect on their pharmacologically isolated GABAergic or glycinergic sIPSCs (Ge et al, 2015 ). Therefore, it is more possible that the inspiratory-related inhibitory inputs of II-AVPNs, which are primarily glycinergic (Hou et al, 2012 ), are somewhat different from the spontaneous inhibitory inputs in respect of the origin, and their inspiratory-related activity may be modulated distinctively.…”
Section: Discussionmentioning
confidence: 99%
“…AVPNs were retrogradely labeled as we have previously described (Chen et al, 2007 , 2012 ; Ge et al, 2015 ). In brief, the 2- to 3-day-old Sprague–Dawley rat was anesthetized with halothane and hypothermia.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Airway vagal preganglionic neurons have been mainly found in the external compact of nucleus ambiguus (eNA) via application of fluorescent tracer to the extrathoracic tracheal wall ( Haselton et al, 1992 ; Haxhiu and Loewy, 1996 ; Kc et al, 2004 ; Chen Y. et al, 2007 ; Qiu et al, 2011 ; Chen et al, 2012a , b ; Hou et al, 2012 , 2015 ; Zhou et al, 2013 ; Ge et al, 2015 ; Guo et al, 2017 ; Yan et al, 2017 ). AVPNs in the eNA function as the main neurons which modulate cholinergic tone of airway smooth muscles as well as control the intrapulmonary airway resistance and tracheobronchial caliber ( Haselton et al, 1992 ; Canning and Fischer, 2001 ; Yan et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%